Strategi Manajemen Keuangan Untuk Pelajar di Era Gen Z Bagi Siswa Smk Islam Darurrohman - Euis Ratnasari; Suripto Muh Zulkifli; Rinaldi Sri Herlambang; Adi Suprayoga; Andri Irawan; Cahyana Cahyana; Rizqi Ikhwanudin Rofif; Nofa Nugraha (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Generation Z refers to the demographic group consisting of individuals born between the mid-1990s to the mid-2010s. This generation is also known as "Gen Z" or "iGen," and they are a group that is growing rapidly in an era of technology and information that continues to develop rapidly. As the first generation to grow up with the internet, social media and mobile technology, Generation Z is considered the most digitally connected group. They are growing up in an era where access to information is easier than ever. Generation Z is also often considered an intelligent, adaptive and collaborative group. They have become a significant marketing target due to their outsized influence on consumer trends and preferences. In addition, Generation Z is faced with various challenges, including preparing themselves for a dynamic job market, facing social and mental pressures, and being responsible for the impact of technology on daily life. Darurrohman Islamic Vocational School is an educational institution that has long been committed to providing high quality education with an Islamic approach to its students. With a strong vision and mission, this school not only focuses on academic aspects, but also pays special attention to the development of students' character and practical skills. The number of participants who took part in this seminar was 69 people. One of the aspects that is really paid attention to at Darurrohman Islamic Vocational School is awareness of financial management in the Gen Z era which is carried out for Darurrohman Islamic Vocational School students as a collaboration between lecturers and students of STIE Ekadharma Indonesia.